Public Speaking Skills Training for Foster Children at UPT Wiloso Projo Child Care Home - Sabrina, Arini; Tur, Ajar Pradika Ananta (Sarana Ilmu Indonesia (salnesia), 2025)
This training activity aimed to enhance the self-confidence and public speaking skills of foster children at the Wiloso Projo Child Care Center through an interactive introduction to English idioms by lecturers and students from LPP Yogyakarta Polytechnic in collaboration with Ahmad Dahlan University. The activity was part of the CHAIN (Chemical Engineering in Action) event series and served as a program of the Community Service Division of HIMATEKIM (Chemical Engineering Student Association) of LPP Yogyakarta Polytechnic. It aimed to improve communication confidence as a vital asset for foster children in pursuing their future, especially considering the current trend that views English communication as prestigious. The training utilized lecture methods and picture-guessing games to enhance participants' understanding of idioms and their pronunciation. The results showed that participants were enthusiastic, actively responded, and demonstrated increased motivation to speak. Ultimately, this activity was expected to inspire similar contributions from academics in other fields.